Dampak Pengendalian Intern dan Ketepatan Informasi Terhadap Kebermanfaatan Akuntansi Akrual: Studi pada Pemerintah Daerah - Fatmawati, Ratna; Setiawan, Doddy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims at examining the effect of internal control and the accuracy of financial reporting information on the usefulness of accrual information for decision-making in Indonesian local governments. The samples of this study are financial officers in the Indonesian local governments. The questionnaires were sent to Regional Work Unit financial officers consisting of Budget Users, Finance Administering officials (PPK) and Treasurers expenditure in six local governments: Surakarta, Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen and Klaten. The 570 questionnaires were sent to the respondenst and only 423 questionnaires that can be used and analysed, resulting in the response rate of 76.31%. A multiple linear regression was utilized for the data analysis. The result of the study shows that the internal controls and the accuracy of financial reporting information have positive influence on the usefulness of accrual accounting information for decision-making in the local governments. Thus, if the level of internal control is higher and the information is more precise, then the information will be more useful for decision-making.